Combining ultrafiltration process with coagulation pretreatment for pulp mill wastewater treatment - Hong, Y S (Environmental technology, 2007)
Ultrafiltration combined with coagulation pretreatment was used to treat two kraft pulp mill wastewaters from first-stage caustic extraction and alkaline bleaching operations, respectively. Both alum and ferric chloride were tested using standard jar apparatus at different dose, pH and ionic strength conditions. Ultrafiltration tests were conducted using a crossflow flat-sheet membrane apparatus operated in the constant transmembrane pressure mode to examine the effects of membrane material, crossflow velocity and transmembrane pressure in terms of permeate flux and treated effluent quality. The results showed that coagulation with both alum and ferric chloride greatly reduced the permeate flux decline rates. In comparison with alum, greater permeate fluxes were obtained with the use of ferric chloride. Among the process parameters examined, coagulant dose was identified as the most important factor affecting the permeate flux. In addition, colour and COD removals were achieved largely by coagulation for alkaline bleaching wastewater while by membrane filtration for caustic extraction wastewater, highlighting the different mechanisms underlying contaminant removal